Preparation method of polymer flexible electrode for all-solid-state lithium battery as well as product and application of polymer flexible electrode

By using polyurethane and LiFePO4 materials to prepare a flexible positive electrode with a porous structure in an all-solid-state lithium battery, the polymer electrolyte solution is cast into the electrode, and bonded with conductive tape to form an integrated flexible positive electrode, which solves the problem of poor interface stability between the electrode and the electrolyte. problem, achieving good electrochemical and safety performance of flexible all-solid-state lithium batteries.

CN119361612APending Publication Date: 2025-01-24SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411835794.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

There are problems of poor interface stability and poor physical contact between the electrodes and electrolytes of existing all-solid-state lithium batteries, resulting in insufficient electrochemical and safety performance.

Method used

The polyurethane is used as the substrate, and the LifePo4 is used as an active substance. By preparing the flexible lithium battery positive film of the porous structure, the polymer electrolyte solution is cast in the electrode, combined with conductive tape adhesion to form an integrated flexible positive electrode, and improves the phase of the electrode and electrolyte. Rongtability and physical contact area.

Benefits of technology

The good electrochemical performance and safety performance of flexible all -solid lithium batteries can be achieved, and it can work normally under the conditions such as folding, bending, cutting, etc., which significantly improves the flexibility and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a polymer flexible electrode for an all-solid-state lithium battery as well as a product and application of the polymer flexible electrode, synthesized polyurethane is taken as a matrix, LiFePO4 is taken as an active substance, a flexible lithium battery positive electrode membrane with a porous structure is prepared firstly, then a polymer electrolyte solution is cast in the prepared porous electrode, and the polymer flexible electrode is prepared. Meanwhile, a conductive adhesive tape is adhered to an electrode film to serve as a current collector to form an integrated flexible positive electrode, and finally the flexible all-solid-state lithium battery is prepared. The solid-state battery can still work under the conditions of folding, bending, shearing and the like, shows good electrochemical performance and safety performance, and has important application value for structural design and performance development of the flexible solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials for solid-state lithium batteries, and in particular to a method for preparing a polymer flexible electrode for an all-solid-state lithium battery, and a product and application thereof. Background Art

[0002] The new energy battery industry has been developing in China for many years. Its market size is second to none in the world. It is an important part of the national economy and has developed global leading enterprises. However, there are still shortcomings in power batteries. There are many reasons for battery spontaneous combustion. Among them, the use of liquid electrolyte is a major drawback. Liquid electrolyte is composed of organic solvents and is very easy to burn. If the lithium battery has thermal runaway during operation, the liquid electrolyte will accelerate the combustion. Solid-state batteries mainly use non-liquid electrolytes, which can improve the safety issues of conventional liquid batteries that are flammable and explosive. Therefore, all-solid-state batteries have become a research hotspot in battery development.

[0003] The flexible all-solid-state batteries reported so far basically adopt the traditional lithium battery assembly method, that is, the positive electrode sheet, electrolyte, and negative electrode sheet are stacked and packaged in three layers. This traditional sandwich structure has solid-solid interface problems between the electrolyte and the electrode, mainly: (1) the electrolyte and the electrode have side reactions due to differences in chemical composition, resulting in poor interface stability; (2) the electrolyte and the electrode have poor physical contact and large interface impedance. To solve these problems, Kim et al. reported in the journal Energy & Environmental Science that by filling the pore space of ceramic fibers with polymer electrolytes and active substances through screen printing technology, a solid-state flexible lithium metal battery with excellent interface stability can be prepared. Ceramic fibers have the characteristics of multi-scale pores, high specific surface area, and high flexibility. Since the same material is used as the polymer skeleton of both the electrode and the electrolyte, the compatibility of the electrode and the electrolyte is improved.

[0004] Thermoplastic polyurethane (TPU) is a highly polar thermoplastic elastomer, which consists of a soft segment and a hard segment. The soft segment is composed of long-chain diols and has a rubbery state at room temperature, which gives TPU good flexibility. The hard segment is composed of diisocyanate and small molecule diamine, which provides high mechanical strength for TPU. Since TPU combines good mechanical properties and dimensional stability and has excellent anti-flexural properties, it is one of the best skeleton materials for preparing flexible batteries. Polyurethane-based flexible porous electrodes have rich pore structures. If a suitable solid electrolyte is selected to fill the pores, it can help increase the physical contact area between the electrode and the electrolyte, which is beneficial to the solid-solid contact between the materials. According to the design and development ideas of solid-state batteries, the present invention discloses a method for preparing a polymer flexible electrode for an all-solid-state lithium battery. The method uses polyurethane as a matrix and LiFePO4 as an active material. First, a flexible lithium battery positive electrode film with a porous structure is prepared, and then a polymer electrolyte solution is cast in the prepared porous electrode. At the same time, a conductive tape is used to bond the electrode film as a current collector to form an integrated flexible positive electrode; then, by assembling with a lithium metal negative electrode, a flexible all-solid-state lithium battery is finally prepared. The solid-state battery can still work under conditions such as folding, bending, and shearing, showing good electrochemical and safety performance. Summary of the invention

[0005] The present invention aims to provide a method for preparing a polymer flexible electrode for an all-solid-state lithium battery.

[0006] Another object of the present invention is to provide a polymer flexible electrode product for an all-solid-state lithium battery prepared by the above method.

[0007] Another object of the present invention is to provide an application of the above product.

[0008] The object of the present invention is achieved by the following scheme: a method for preparing a polymer flexible electrode for an all-solid-state lithium battery, using a synthetic polyurethane as a matrix and LiFePO4 as an active material, first preparing a flexible lithium battery positive electrode film with a porous structure, then casting a polymer electrolyte solution in the prepared porous electrode, and at the same time using a conductive tape to bond to the electrode film as a current collector to form an integrated flexible positive electrode, and finally preparing a flexible all-solid-state lithium battery, the specific steps are as follows: a. Preparation of polyurethane polymer solid electrolyte membrane: First, the polyurethane prepolymer was synthesized, and the mass ratio of isoflurane diisocyanate (IPDI): polyethylene glycol (PEG): polyoxypropylene glycol (PPG) = 10:1:0.5 was weighed, and the temperature was raised to 90°C under vacuum to further remove moisture, and a prepolymerization reaction was carried out. After the emulsion was formed, a small amount of ethylenediamine was added to adjust the viscosity to obtain a polyurethane prepolymer, and the molecular weight of the polyurethane TPU prepolymer was controlled within an appropriate range. Then, the polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane was prepared, and the polyurethane prepolymer, polyoxyethylene (PEO) solution and lithium bistrifluoromethanesulfonate imide (LiTFSI) were mixed in a mass ratio of 3:1:1, and after being stirred uniformly, poured onto the surface of a polytetrafluoroethylene plate, coated on the polytetrafluoroethylene plate with a 200 μm scraper, dried at room temperature to form a film, and the composite film was dried in a vacuum oven. The sample was stored in a glove box to obtain a polyurethane polymer electrolyte membrane; b. Preparation of porous flexible cathode membrane: First, the polyurethane TPU prepared in step a was dissolved in N,N-dimethylformamide (DMF) solvent to prepare a 15wt% glue solution. Then, the raw materials were weighed and slurried according to the ratio of LiFePO4: TPU glue solution: conductive carbon black = 6:3:1. The mixed slurry was applied to a polytetrafluoroethylene plate with a 300 μm scraper and placed in a water bath for 4 h. As DMF evaporated, the slurry gradually solidified into a flexible film. The flexible film that completed the phase inversion was peeled off from the plate, washed with ethanol and deionized water 3 times, and then dried to obtain a porous flexible positive electrode membrane.

[0009] c. Improvement of porous flexible cathode membrane (i.e. preparation of integrated porous flexible cathode membrane): The polyurethane prepolymer, PEO solution, lithium bis(trifluoromethanesulfonate imide) LiTFSI and nano-SiO2 are mixed and stirred in a ratio of 3:1:1:0.5 to form a glue solution, which is then poured on the surface of the porous flexible cathode membrane. At the same time, a conductive tape is used as a current collector to bond it to the electrode membrane. After drying for 24 hours, it is transferred to a vacuum drying oven and dried at 80°C for 4 hours. Finally, the sample is stored in a glove box to obtain an improved porous flexible cathode membrane (i.e., an integrated porous flexible cathode membrane).

[0010] d. Assembly of flexible all-solid-state lithium battery: Using lithium metal as the negative electrode, the above-mentioned integrated porous flexible positive electrode membrane and solid polymer electrolyte membrane are assembled and combined to prepare a flexible all-solid-state soft-pack lithium battery according to size.

[0011] The isophorone diisocyanate (IPDI) used in the present invention is a material with a molecular weight of Mw=230, and the polyethylene oxide (PEO) used is a material with a molecular weight of Mw=500000; The molecular weight Mw of the polyurethane prepolymer prepared in step a of the present invention is controlled within the range of 25000 to 27000; The polyurethane prepolymer, PEO solution, lithium bis(trifluoromethanesulfonate imide) LiTFSI and nano-SiO2 used in the present invention are mixed and stirred in a ratio of 3:1:1:(0.2-0.5). The present invention provides a polymer flexible electrode for an all-solid-state lithium battery, which is characterized in that it is prepared according to any of the above methods. The present invention provides an application of a polymer flexible electrode in a flexible all-solid-state lithium battery material.

[0012] The present invention mainly utilizes the combination of soft segments and hard segments of polyurethane, takes LiFePO4 as the active component, prepares a flexible lithium battery positive electrode membrane with a porous structure, and cleverly casts the polymer electrolyte solution into the prepared porous electrode to obtain an integrated flexible positive electrode, thereby preparing a flexible all-solid-state lithium battery. This provides a method for preparing a polymer flexible electrode for an all-solid-state lithium battery, which has important guiding significance for the development of flexible solid-state lithium batteries.

[0013] This method casts the modified polyurethane polymer solid electrolyte inside the flexible porous electrode positive electrode membrane to form a flexible all-solid-state lithium battery with an integrated positive electrode / solid electrolyte design. The solid-state battery can still work under conditions such as folding, bending, and shearing, showing good electrochemical and safety performance, which has important application value for the structural design and performance development of flexible solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The scanning electron microscope spectrum of the prepared integrated porous flexible cathode membrane; Figure 2 This is the charge and discharge performance spectrum of the flexible all-solid-state lithium battery assembled using this material. DETAILED DESCRIPTION

[0015] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0016] Example 1 A polymer flexible electrode for an all-solid-state lithium battery, with a synthetic polyurethane TPU as a matrix and LiFePO4 as an active material, first prepares a flexible lithium battery positive electrode film with a porous structure, then casts a polymer electrolyte solution in the prepared porous electrode, and uses a conductive tape to bond the electrode film as a current collector to form an integrated flexible positive electrode, and prepares a flexible all-solid-state lithium battery, which is prepared according to the following steps: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90 °C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 25000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and use 200 The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. Preparation of porous flexible positive electrode membrane: first, the polyurethane TPU prepolymer prepared in step a is dissolved in N,N-dimethylformamide (DMF) solvent to prepare a 15 wt% glue solution; then, 6 g of LiFePO4, 3 g of TPU glue solution and 1 g of conductive carbon black are weighed for slurry preparation, and the mixed slurry is applied on a polytetrafluoroethylene plate with a 300 μm scraper, and placed in a water bath for 4 h; as DMF evaporates, the slurry gradually solidifies into a layer of flexible membrane; the flexible membrane that has completed the phase inversion is peeled off from the plate, washed with ethanol and deionized water 3 times, and dried to obtain a porous flexible positive electrode membrane; c. Improvement of porous flexible positive electrode membrane: 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 0.4 g of nano-SiO2 were weighed and mixed to form a glue solution, which was then poured on the surface of the porous flexible positive electrode membrane prepared in step b. At the same time, a conductive tape was used as a current collector to bond the porous flexible positive electrode membrane. After drying for 24 h, the tape was transferred to a vacuum drying oven and dried at 80°C for 4 h. Finally, the sample was stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane. d. Assembly of flexible all-solid-state lithium battery: Using lithium metal as the negative electrode, the integrated porous flexible positive electrode membrane prepared above and the solid polymer electrolyte membrane are assembled to prepare a flexible all-solid-state soft-pack lithium battery, and electrochemical performance tests are performed at the same time.

[0017] Figure 1The scanning electron microscope spectrum of the preparation of the integrated porous flexible positive electrode membrane. It can be seen from the figure that LiFePO4, SiO2 particles and high molecular weight TPU polymer are tightly combined together. At the same time, there are many fine channels inside the TPU polymer, showing a high porosity, which is conducive to the transmission of electrons. The positive electrode membrane structure can be bent and folded, highlighting the good flexibility. At the same time, due to the addition of SiO2 fine particles, the material forms a continuous skeleton network, which makes the material also have strong mechanical strength.

[0018] Figure 2 This is the charge and discharge performance spectrum of the flexible all-solid-state lithium battery assembled with this material. When the conductive glue is used as the current collector, the prepared all-solid-state lithium battery can still discharge 58 mAh g at a current of 5C. -1 The specific capacity shows good battery performance.

[0019] Embodiment 2: A polymer flexible electrode for an all-solid-state lithium battery, step a is the same as in Example 1, except that the molecular weight Mw of the polyurethane is controlled to be 26000; step b is the same as in Example 1, and is prepared according to the following steps: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90 °C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 26000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and 200 g of ethylenediamine was used to prepare polyurethane prepolymer. The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. The same as in Example 1, a porous flexible positive electrode membrane is prepared; c. Improvement of porous flexible positive electrode membrane: 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 0.6 g of nano-SiO2 were accurately weighed and mixed to form a glue solution, which was then poured on the surface of the porous flexible positive electrode membrane prepared in step b. A conductive tape was used as a current collector to bond the electrode membrane. After drying for 24 h, the mixture was transferred to a vacuum drying oven and dried at 80°C for 4 h. The obtained composite membrane sample was stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane. d. As in Example 1, a flexible all-solid-state lithium battery was assembled and electrochemical performance tests were performed simultaneously.

[0020] Embodiment 3: A polymer flexible electrode for an all-solid-state lithium battery, step a is the same as in Example 1, except that the molecular weight Mw of the polyurethane is controlled to be 28000; step b is the same as in Example 1, and is prepared according to the following steps: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90°C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 28000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and use 200 The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. The same as in Example 1, a porous flexible positive electrode membrane is prepared; c. Improvement of porous flexible positive electrode membrane: 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 1 g of nano-SiO2 were accurately weighed and mixed to form a glue solution, which was then poured on the surface of the porous flexible positive electrode membrane prepared in step b. A conductive tape was used as a current collector to bond the positive electrode membrane. After drying for 24 h, the mixture was transferred to a vacuum drying oven and dried at 80°C for 4 h. The obtained composite membrane sample was stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane. d. As in Example 1, a flexible all-solid-state lithium battery was assembled and electrochemical performance tests were performed simultaneously.

Claims

1. A method for preparing a polymer flexible electrode for an all-solid-state lithium battery, characterized in that With the synthesized polyurethane TPU as the matrix and LiFePO4 as the active material, a flexible lithium battery positive electrode film with a porous structure is first prepared, and then a polymer electrolyte solution is cast in the prepared porous electrode, and a conductive tape is used to bond the electrode film as a current collector to form an integrated flexible positive electrode, and a flexible all-solid-state lithium battery is prepared, which includes the following steps: a. Preparation of polyurethane polymer solid electrolyte membrane: Firstly, a polyurethane prepolymer is synthesized, and isoflurane diisocyanate (IPDI): polyethylene glycol (PEG): polyoxypropylene glycol (PPG) are mixed in a mass ratio of 10:1:0.5, and then the mixture is heated to 90°C by vacuum condensation to remove moisture and perform a prepolymerization reaction. After an emulsion is formed, ethylenediamine is added to adjust the viscosity to obtain a polyurethane prepolymer. Then, a polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane is prepared, and a polyurethane prepolymer, a polyoxyethylene (PEO) solution and lithium bistrifluoromethanesulfonimide (LiTFSI) are mixed in a mass ratio of 3:1:1, and after being stirred evenly, the mixture is poured onto the surface of a polytetrafluoroethylene plate, and then coated on the polytetrafluoroethylene plate with a 200 μm scraper, and then dried at room temperature to form a composite membrane. The composite membrane is dried in a vacuum oven, and the obtained sample is stored in a glove box to obtain a polyurethane solid polymer electrolyte membrane. b. Preparation of porous flexible cathode membrane: First, the polyurethane TPU prepared in step a is dissolved in N, N-dimethylformamide (DMF) solvent to prepare a 15 wt% glue solution, and then mixed and slurried according to the mass ratio of LiFePO4: TPU glue solution: conductive carbon black of 6:3:

1. The mixed slurry is applied on a polytetrafluoroethylene plate with a 300 μm scraper and placed in a water bath for 4 hours. As DMF evaporates, the slurry gradually solidifies into a layer of flexible film. The flexible film that has completed the phase inversion is peeled off from the plate, washed with ethanol and deionized water, and dried to obtain a porous flexible positive electrode membrane. c. Improvement of porous flexible cathode membrane: The polyurethane prepolymer, PEO solution, lithium bis(trifluoromethanesulfonate imide) LiTFSI and nano-SiO2 were mixed and stirred in a mass ratio of 3:1:1:(0.2-0.5) to form a glue solution, which was then poured on the surface of the porous flexible cathode film. At the same time, a conductive tape was used as a current collector to bond the electrode film. After drying for 24 hours, the sample was transferred to a vacuum drying oven and dried at 80°C for 4 hours. The sample was then stored in a glove box to obtain an improved integrated porous flexible cathode film. d. Assembly of flexible all-solid-state lithium battery: Using lithium metal as the negative electrode, the above-mentioned integrated porous flexible positive electrode membrane and solid polymer electrolyte membrane are assembled to prepare a flexible all-solid-state soft-pack lithium battery.

2. The method for preparing a polymer electrolyte for a flexible solid-state lithium battery according to claim 1, characterized in that: The molecular weight of isophorone diisocyanate (IPDI) is Mw=230, and the molecular weight of polyethylene oxide (PEO) is Mw=500000.

3. The method for preparing a polymer electrolyte for a flexible solid-state lithium battery according to claim 1, characterized in that In step a, the molecular weight Mw of the polyurethane prepolymer is controlled in the range of 25000 to 28000.

4. The method for preparing a polymer electrolyte for a flexible solid-state lithium battery according to any one of claims 1 to 3, characterized in that: Prepare as follows: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90 °C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 25000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and use 200 The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. Preparation of porous flexible positive electrode membrane: first, the polyurethane TPU prepolymer prepared in step a is dissolved in N,N-dimethylformamide (DMF) solvent to prepare a 15 wt% glue solution; then, 6 g of LiFePO4, 3 g of TPU glue solution and 1 g of conductive carbon black are weighed for slurry preparation, and the mixed slurry is applied on a polytetrafluoroethylene plate with a 300 μm scraper, and placed in a water bath for 4 h; as DMF evaporates, the slurry gradually solidifies into a layer of flexible membrane; the flexible membrane that has completed the phase inversion is peeled off from the plate, washed with ethanol and deionized water 3 times, and dried to obtain a porous flexible positive electrode membrane; c. Improvement of porous flexible positive electrode membrane: 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 0.4 g of nano-SiO2 were weighed and mixed to form a glue solution, which was then poured on the surface of the porous flexible positive electrode membrane prepared in step b. At the same time, a conductive tape was used as a current collector to bond the porous flexible positive electrode membrane. After drying for 24 h, the tape was transferred to a vacuum drying oven and dried at 80°C for 4 h. Finally, the sample was stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane. d. Assembly of flexible all-solid-state lithium battery: Using lithium metal as the negative electrode, the integrated porous flexible positive electrode membrane prepared above and the solid polymer electrolyte membrane are assembled to prepare a flexible all-solid-state soft-pack lithium battery.

5. The method for preparing a polymer electrolyte for a flexible solid-state lithium battery according to any one of claims 1 to 3, characterized in that: Prepare as follows: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90 °C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 26000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and 200 g of ethylenediamine was used to prepare polyurethane prepolymer. The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. Prepare a porous flexible cathode film; c. Improvement of porous flexible positive electrode membrane: 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 0.6 g of nano-SiO2 were accurately weighed and mixed to form a glue solution, which was then poured on the surface of the porous flexible positive electrode membrane prepared in step b. A conductive tape was used as a current collector to bond the electrode membrane. After drying for 24 h, the mixture was transferred to a vacuum drying oven and dried at 80°C for 4 h. The obtained composite membrane sample was stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane. d. Assemble a flexible all-solid-state lithium battery to obtain a flexible all-solid-state soft-pack lithium battery.

6. The method for preparing a polymer electrolyte for a flexible solid-state lithium battery according to any one of claims 1 to 3, characterized in that: Prepare as follows: a. Preparation of polyurethane polymer solid electrolyte membrane: firstly, synthesize polyurethane prepolymer, weigh 100 g isoflurane diisocyanate (IPDI), 10 g polyethylene glycol (PEG) and 5 g polyoxypropylene glycol (PPG), mix them, add them into a four-necked flask and build a reflux condenser, heat to 90 °C under vacuum to further remove moisture, and carry out prepolymerization reaction at the same time. After the emulsion is formed, add 2 g ethylenediamine, adjust the viscosity to obtain polyurethane prepolymer, and control the molecular weight Mw of polyurethane to 28000; then prepare polyurethane TPU / polyoxyethylene PEO composite polymer electrolyte membrane, weigh 6 g of the prepared polyurethane prepolymer, 2 g of polyoxyethylene (PEO) solution and 2 g of lithium bis(trifluoromethanesulfonic acid imide) (LiTFSI), mix them, pour them onto the surface of polytetrafluoroethylene plate after stirring evenly, and use 200 The polyurethane solid polymer electrolyte membrane is obtained by coating the composite film with a scraper of μm on a polytetrafluoroethylene plate and drying it at room temperature. The composite film is dried in a vacuum oven and stored in a glove box. b. Prepare a porous flexible cathode film; c. Improvement of porous flexible positive electrode membrane: accurately weigh 6 g of polyurethane prepolymer prepared in step a, 2 g of polyethylene oxide, 2 g of lithium bis(trifluoromethanesulfonate imide) LiTFSI and 1 g of nano-SiO2, mix and stir to form a glue solution, and then pour it on the surface of the porous flexible positive electrode membrane prepared in step b. At the same time, use a conductive tape as a current collector to bond the positive electrode membrane. After drying for 24 hours, transfer it to a vacuum drying oven and dry it at 80°C for 4 hours. The obtained composite membrane sample is stored in a glove box to obtain an improved integrated porous flexible positive electrode membrane; d. Assemble a flexible all-solid-state lithium battery to obtain a flexible all-solid-state soft-pack lithium battery.

7. A polymer flexible electrode for an all-solid-state lithium battery, characterized in that Prepared according to any one of claims 1 to 6.

8. Use of the polymer flexible electrode according to claim 7 in flexible all-solid-state lithium battery materials.